2017
DOI: 10.1016/j.jhep.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Objective response by mRECIST as a predictor and potential surrogate end-point of overall survival in advanced HCC

Abstract: NCT00825955.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
165
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 197 publications
(177 citation statements)
references
References 41 publications
12
165
0
Order By: Relevance
“…Multivariable analysis showed that response according to mRECIST was an independent predictor of survival, albeit only with a trend toward significance (HR 0.62, 95% CI 0.38-1.01, p = 0.053), roughly supporting the results of the multivariable analysis reported by Lencioni et al [8]. Kudo et al [10] conducted the SILIUS study (a prospective controlled trial), and reported that 18 out of 96 patients who received sorafenib monotherapy were responders (response rate, 18.8%); OS was 27.2 months in these patients, which was significantly longer than the OS of 8.9 months in nonresponders (p < 0.001).…”
Section: Association Between Response To Molecular Targeted Agents Ansupporting
confidence: 84%
See 1 more Smart Citation
“…Multivariable analysis showed that response according to mRECIST was an independent predictor of survival, albeit only with a trend toward significance (HR 0.62, 95% CI 0.38-1.01, p = 0.053), roughly supporting the results of the multivariable analysis reported by Lencioni et al [8]. Kudo et al [10] conducted the SILIUS study (a prospective controlled trial), and reported that 18 out of 96 patients who received sorafenib monotherapy were responders (response rate, 18.8%); OS was 27.2 months in these patients, which was significantly longer than the OS of 8.9 months in nonresponders (p < 0.001).…”
Section: Association Between Response To Molecular Targeted Agents Ansupporting
confidence: 84%
“…Lencioni et al [8] performed a responder analysis using data from a Phase III trial of brivanib as second-line therapy. Among 226 brivanib-treated patients, 26 were responders according to mRECIST (ORR 11.5%); OS was 15.0 months in responders, which was significantly longer than the OS of 9.4 months in nonresponders (HR 0.31, 95% CI 0.16-0.60, p < 0.001).…”
Section: Association Between Response To Molecular Targeted Agents Anmentioning
confidence: 99%
“…In one of these studies, Lencioni et al [6] used data from a phase III comparative study of second-line treatment with brivanib to analyze responders using mRECIST. They found a response (mRECIST) in 11.5% (26/226) of patients receiving brivanib, and these responders to brivanib therapy clearly survived significantly longer than nonresponders (15.0 vs. 9.4 months; hazard ratio [HR] 0.31; 95% CI 0.16–0.60; p < 0.001) by landmark analysis at 15 months.…”
Section: Association Between Objective Response and Overall Survival mentioning
confidence: 99%
“…Multivariate analysis with time-dependent covariates also clearly demonstrated that objective response based on mRECIST was an independent prognostic factor. In the discussion section of their report, Lencioni et al [6] state that the level of evidence of this study is high due to the phase III randomized controlled nature of the original study.…”
Section: Association Between Objective Response and Overall Survival mentioning
confidence: 99%
“…A very recent and interesting analysis on the population of the second-line Phase III BRISK study showed that response according to the mRECIST was an independent predictor of OS in patients treated with anti-VEGFR agents [66]. However, the performance of mRECIST was not compared with RECIST.…”
Section: Radiologic Criteria Of Responsementioning
confidence: 99%